PARACONTACT METRIC (?, µ) R-HARMONIC MANIFOLDS - Erken, İrem Küpeli (Univ Kragujevac, Fac Science, 2020)
We give classifications of paracontact metric ((kappa) over tilde,(mu) over tilde) manifolds M2n+1 with harmonic curvature for n > 1 and n = 1.
Keywords: Paracontact metric manifolds; R-harmonic manifold; (kappa, mu)-nullity distribution